Folate biofortification in food crops. (April 2017) - Strobbe, Simon; Van Der Straeten, Dominique
Graphical abstract: Highlights: Folates are an essential part of the human diet. Many staple crops contain insufficient folate levels. Folate biofortification of rice yields levels satisfying the daily requirement. Increasing folate stability was shown to be successful in rice. Hurdles remain in extrapolation of engineering strategies to other staple crops. Abstract : Folates are essential vitamins in the human diet. Folate deficiency is still very common, provoking disorders such as birth defects and anemia. Biofortification via metabolic engineering is a proven powerful means to alleviate folate malnutrition. A variety of metabolic engineering approaches have been successfully implemented in different crops and tissues. Furthermore, ensuring folate stability is crucial for long-term storage of crop products. However, the current strategies, shown to be successful in rice and tomato, will need to be fine-tuned to enable adequate biofortification of other staples such as potato, wheat and cassava. Thus, there is a need to overcome remaining hurdles in folate biofortification. Overall, biofortification, via breeding or metabolic engineering, will be imperative to effectively combat folate deficiency.